Designing an e-democracy framework to enhance the Egyptian e-government (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
E-democracy concept can enhance Egyptian participation in rule and it can move e-the Egyptian government to a new era. E-democracy concept can be applied in conjunction with database connection to transfer Egyptian e-government to transformation stage. This Paper concentrates mainly on designing an e-democracy framework using two case studies in e-government systems .As we will see system is web based application based .There are some figures that describe system architecture then each component well be explained. The framework technical aspects, analysis and objectives in establishing integrated e-government will be discussed.Â